Ellipsoidal estimation of parameters of rotational and translational motion of a non-cooperative space vehicle from visual information - Salnikov, N.; Melnychuk, S.; Gubarev, V. (Проблеми керування та інформатики, 2023)
This work considers the most general case of the relative motion of servicing spacecraft (SSC) and non-cooperative spacecraft (NSC). Using quaternion calculus, all basic kinematic and dynamic equations are obtained. The results obtained are expected to be used in the development, creation and testing of a navigation system for the rendezvous and docking of the SSC, developed by a group of Ukrainian space industry enterprises under the leadership of the LLC «Kurs-orbital» (https://kursorbital.com/). У даній роботі розглядається найбільш загальний випадок відносного руху сервісного космічного апарату (СКА) і некооперативного космічного апарату (НКА). За допомогою кватерніонного числення отримано всі основні кінематичні та динамічні рівняння. Отримані результати планується використати при розробці, створенні та випробуванні навігаційної системи зближення та стикування СКА, який розробляється групою підприємств космічної галузі України під керівництвом ТОВ «Курс-орбітал» (https://kursorbital.com/).